Giant esophageal fibrovascular polyp with clinical behaviour of inflammatory pseudotumor: A case report and the literature review - Ćuk, Vladimir; Knežević - Ušaj, Slavica; Ignjatović, Mile; Kostić, Zoran; Tarabar, Dino; Kovačević, Bojan; Šćepanović, Milena; Slavković, Damjan (Vojnosanitetski pregled, 2014)
Introduction. Esophageal fibrovascular polyps are rare, benign, intraluminal, submucosal tumor-like lesions, characterized by pedunculated masses which can demonstrate enormous growth. The most frequent symptoms are dysphagia, vomiting and weight loss. Fibrovascular polyps with long stalks can regurgitate into the airways and cause asphyxia. Esophageal inflammatory pseudotumor is extremely rare lesion accompanied with various systemic manifestations as fever, anemia and thrombocytosis. Case report. We presented a 29-year-old man complaining of a long-lasting fever and dysphagia. He was found to have huge pedunculated submucosal tumor of esophagus, surgically completely resected. Histopathological examination showed that this giant tumor, 24 ´ 9 ´ 6 cm, was a fibrovascular polyp. The postoperative course was uneventful. The preoperative fever, anemia and thrombocytosis disappeared and did not recur in the postoperative course. Conclusion. We reported a patient with giant esophageal pedunculated tumor with clinical manifestations of inflammatory pseudotumor and histopathological picture of fibrovascular polyp, that we have not found described in the literature before.
Keywords: polyps; esophagus; granuloma; plasma cell; diagnosis; endosonography; histological techniques; surgical procedures; operative; treatment outcome